The Expression Regulatory Network in the Lung Tissue of Tibetan Pigs Provides Insight Into Hypoxia-Sensitive Pathways in High-Altitude Hypoxia - Yang, Yanan; Yuan, Haonan; Yang, Tianliang; Li, Yongqing; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Genetics, 2021)
To adapt to a low-oxygen environment, Tibetan pigs have developed a series of unique characteristics and can transport oxygen more effectively, but the regulation of the associated processes in high-altitude animals remains elusive. We performed mRNA-seq and miRNA-seq and constructed coexpression regulatory networks in the lung tissues of Tibetan pigs and Landrace pigs. Pathways related to major regulators of hypoxia-induced genes, signal transduction and angiogenesis were enriched, including HIF-1, PI3K-Akt, mTOR and AMPK. HBB, AGT, COL1A2 and EPHX1 were identified as key genes that regulate blood pressure and circulation. AHSP, HBB, HP, VEGF, and ANG may promote the combination of hemoglobin and oxygen and angiogenesis for high-altitude adaptation in Tibetan pigs. These findings provide a perspective on hypoxia-adaptive genes in the lungs and insight into potential candidate genes in Tibetan pigs for further research in the field of high-altitude adaptation.